1994
DOI: 10.1007/bf00865479
|View full text |Cite
|
Sign up to set email alerts
|

Improved neurological outcome in children with chronic renal disease from infancy

Abstract: Progressive encephalopathy, developmental delay, microcephaly, electroencephalogram (EEG) and computed tomographic (CT) scan abnormalities have been reported in 80% of children with chronic renal failure (CRF) in infancy. Malnutrition, aluminium intoxication and psychosocial deprivation are proposed as causes. In 15 children with CRF from infancy we evaluated the effect of no aluminium salts and early vigorous nutritional and psychosocial support, in addition to the standard therapy, on neurological developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 30 publications
5
34
1
Order By: Relevance
“…General muscular hypotonia has also been observed in nine, four, and two children with chronic kidney disease, on dialysis, and after RTPL, respectively [6]. Motor performance assessed by the Bayley Scales of Infant Development was normal in 76% of children transplanted at an age < 5 years, and similar to our own findings, neurological comorbidity was the most negative predictor [9].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…General muscular hypotonia has also been observed in nine, four, and two children with chronic kidney disease, on dialysis, and after RTPL, respectively [6]. Motor performance assessed by the Bayley Scales of Infant Development was normal in 76% of children transplanted at an age < 5 years, and similar to our own findings, neurological comorbidity was the most negative predictor [9].…”
Section: Discussionsupporting
confidence: 68%
“…patient and graft survival, has steadily improved over the last decades [23,24]. However, information on comprehensive and detailed neurodevelopmental outcome after RTPL is still limited [1][2][3][4][5][6][7][8][9]. This cross-sectional study presents detailed measures of IP and MP in children after RTPL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few other studies have examined motor performance in this population. General muscular hypotonia has been a consistent finding in many children with chronic kidney diseases of various origins [40]. Muscular hypotonia can be associated with poorer motor perfor- mance, in particular with static balance tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with their age-matched controls, the renal patients had significantly enlarged ventricles, with the greatest enlargement noted in the HD group. Using a small sample of pediatric patients who developed CKD at birth, Elzouki and colleagues (47) found that approximately 23% showed cerebral atrophy. Enlarged ventricles, a correlate of brain atrophy, have also been reported by investigators studying primarily pediatric samples; estimates were significantly higher and ranged from 59% (44) to 67% (43).…”
Section: Findings In Pediatric Structural Neuroimaging Studiesmentioning
confidence: 99%